Inoperable Renal Malignant Glomus Tumor, the answers for all the “W’s”? (Journal of Kidney Cancer, 2024)
Glomus tumor, arising from glomus bodies (specialized neurovascular structures involved in thermoregulation), commonly occurs in extremities and rarely in viscera. The spectrum of glomus tumors range from benign tumors to tumors with uncertain malignant potential to tumors of the malignant subtype. A vast majority of visceral glomus tumors are benign. Most common visceral tumors arise in the gastrointestinal tract. Glomus tumors of the kidney are a rare entity of which malignant glomus tumors are exceedingly rare. The index patients in the existing case reports were middle-aged males. We report our experience with malignant glomus tumor of the left kidney in a 60-year-old female, with computed tomography (CT) showing involvement of renal vein and inferior vena cava (IVC). Percutaneous biopsy was performed as imaging did not conform to the appearance of a conventional renal tumor and was reported as malignant glomus tumor after immunohistochemistry. After informed decision, the patient and family elected to proceed with surgery. However, intraoperatively, the left renal mass was found to infiltrate the pancreas, duodenum, aorta, and root of the colonic mesentery due to which surgery was aborted. Biopsy obtained intraoperatively again confirmed diagnosis of left renal malignant glomus tumor. She had an uneventful postoperative recovery. Options of treatment were reviewed by a multidisciplinary board. In light of no proven benefit for systemic therapy, she was referred for supportive care. She was under follow-up and she expired after 7 months due to progressive disease. Our literature review focuses on the clinicopathologic features and the current standard of management of malignant renal glomus tumors.